Investigating the Influence of Tube Voltage and Current Variations on CT Number-RED Conversion Curves for Radiotherapy CT Scanner - Kaduga Altwieb,; Ahmed Alghfod,; Mohanned Alrtemy,; Feras Alshkery,; Basher Hamed,; Alzarouq Eherz, (AlQalam Journal of Medical and Applied Sciences, 2024)
CT simulation is the first chain in radiotherapy treatment, the patient image is acquired by CT scanner to determine the exact location and densities of patient organs in specific coordinate called Pixel, each pixel has a unit called CT number or Hounsfield unit (HU) which representing the linear attenuation coefficient value of X-ray beam that interacts with each different tissue density. on the other hand, Electron density (ED) is the number of electrons contained by certain tissue of specific density, the ratio between each tissue electron density and water electron density is called relative electron density (RED), the conversion curve between CT number and RED should be measured and transferred to the treatment planning system (TPS) which are then used in the dose calculation algorithms. This study aims to evaluate how variations in tube voltage and current affect CT number-RED conversion curves. Utilizing a GE Lightspeed-RT CT scanner and CIRS (062M) phantom with inserts of diverse tissue densities, images were obtained at tube voltages of 80, 100, 120, and 140kV, at constant settings of tube currents ranging from 50 to 380mA, and vice versa. CT number mean and standard deviation were recorded for all inserts at different settings using Micro Dicom viewer software. Tube voltage variation at constant current affected high RED materials (dense bone), while tube current variation at constant voltage minimally impacted the CT-RED curve, except at low tube voltage (80kV). Considering evidence from this study and other studies on CT number's influence on dose calculation, it is advisable to account for scanner settings and specific CT-ED look-up tables, particularly in scenarios involving high-density materials, for accurate radiotherapy treatment planning محاكاة الأشعة المقطعية هي السلسلة الأولى في علاج العلاج الإشعاعي، حيث يتم التقاط صورة المريض بواسطة ماسح الأشعة المقطعية لتحديد الموقع الدقيق وكثافات أعضاء المريض في إحداثيات محددة تسمى بكسل، ولكل بكسل وحدة تسمى رقم الأشعة المقطعية أو وحدة هاونسفيلد (HU) والتي تمثل قيمة معامل التوهين الخطي لحزمة الأشعة السينية التي تتفاعل مع كل كثافة أنسجة مختلفة. من ناحية أخرى، كثافة الإلكترون (ED) هي عدد الإلكترونات الموجودة في أنسجة معينة ذات كثافة محددة، وتسمى النسبة بين كثافة إلكترون كل نسيج وكثافة إلكترون الماء بالكثافة الإلكترونية النسبية (RED)، ويجب قياس منحنى التحويل بين عدد CT وRED ونقله إلى نظام تخطيط العلاج (TPS) والذي يُستخدم بعد ذلك في خوارزميات حساب الجرعة. تهدف هذه الدراسة إلى تقييم كيفية تأثير الاختلافات في جهد الأنبوب والتيار على منحنيات تحويل عدد CT إلى RED. باستخدام ماسح CT GE Lightspeed-RT وشبح CIRS (062M) مع إدخالات بكثافات أنسجة متنوعة، تم الحصول على الصور عند جهد أنبوبي 80 و100 و120 و140 كيلو فولت، عند إعدادات ثابتة لتيارات الأنبوب تتراوح من 50 إلى 380 مللي أمبير، والعكس صحيح. تم تسجيل متوسط ​​عدد CT والانحراف المعياري لجميع الإدخالات في إعدادات مختلفة باستخدام برنامج Micro Dicom viewer. أثرت التغيرات في جهد الأنبوب عند تيار ثابت على المواد عالية الكثافة الحمراء (العظام الكثيفة)، بينما أثرت التغيرات في تيار الأنبوب عند جهد ثابت بشكل طفيف على منحنى CT-RED، باستثناء الجهد المنخفض للأنبوب (80 كيلو فولت). بالنظر إلى الأدلة من هذه الدراسة وغيرها من الدراسات حول تأثير رقم CT على حساب الجرعة، فمن المستحسن مراعاة إعدادات الماسح الضوئي وجداول البحث CT-ED المحددة، وخاصة في السيناريوهات التي تنطوي على مواد عالية الكثافة، من أجل التخطيط الدقيق لعلاج العلاج الإشعاعي